Survei Kepuasan Kader dalam Penggunaan Aplikasi iPosyandu dalam Pelayanan Kesehatan Ibu dan Anak di Indonesia: Cadre Satisfaction Survey in Using iPosyandu Application for Maternal and Child Health Services in Indonesia - Atriany Nilam Sari; Ari Indra Susanti; Fedri Ruluwedrata Rinawan (Jurnal Bidan Cerdas, 2021)
Introduction: iPosyandu application was initially developed to answer the problems of cadres in recording and reporting Posyandu who still use aid book, so there was often delay in reporting to the Puskesmas, with late reports, information was difficult to obtain. This study aims to find out the satisfaction of cadres in using the iPosyandu application. Methods: This research used descriptive cross-sectional approach, and was conducted from July to December 2020, followed by 251 posyandu cadres spread across in Indonesia. This sampling uses accidental sampling method that meets the research criteria. Data retrieval using online survey questionnaire satisfaction of iPosyandu application. Data analysis using univariate with descriptive statistics accompanied by Importance Performance Analysis (IPA) method. Results: This study showed the dimension that is the top priority for immediate improvement is the accuracy dimension with the data accuracy item of posyandu information system on iPosyandu application. Conclusion: Accurate data is useful as a source of information and accuracy in interpreting maternal and child health data in the region.